PENGARUH BRAND IMAGE DALAM MEMEDIASI PENGARUH KUALITAS PRODUK TERHADAP NIAT BELI ULANG - Dika Ardimas Sanjaya, Kadek; Ardani, I Gst. A.Kt. Sri (E-Jurnal Manajemen; Vol 7 No 11 (2018)DO - 10.24843/EJMUNUD.2018.v07.i11.p13, 2018)
The purpose of this study To explain the effect of pocari sweat product quality on brand image, the effect of pocari sweat product quality on repurchase intention, the effect of pocari sweat brand image to repurchaseintention in Denpasar city, the effect of brand image in mediating pocari sweat product quality to purchase intention at city ??of Denpasar. Respondents in the researcher is on consumers who have ever bought isotonic drink products Pocari Sweat in Denpasar City. The number of samples is 108 respondents, with purposive sampling method. The data were collected through questionnaires, interviews, and observations. Analytical technique used is path analysis, showing that: (1) product quality have positive and significant effect to brand image; (2) product quality has a positive and significant effect on repurchase intention; (3) the brand image has a positive and significant impact on repurchase intention; (4) brand image acts as a mediating variable between product quality variables and repurchase intention. The findings of this study conclude that product quality has a positive and significant effect on brand image and consumer buy-back intention to isotonic pocari sweat drink product in Denpasar city, brand image is able to mediate product quality to repurchase intention. Keywords: brand image, product quality, repurchase intention